Thermodynamic efficiency of membrane separation of dilute gas: Estimation for CO2 direct air capture application - Masaki Kato; Teruki Ando; Cho Rong Kim; Seiya Yokokura; Hiroki Waizumi; Toshihiro Shimada (Journal of Membrane Science Letters)
Gas separation technology is crucial for addressing environmental issues like CO2 capture to mitigate climate change. While membrane separation is often cited for its efficiency, accurate estimations are scarce. We present estimations based on classical thermodynamics for very lean CO2 composition (400 ppm), revealing rich details in simple systems and deriving guiding principles. Our main conclusion emphasizes the critical necessity of a high membrane separation ratio, and we discuss candidates for achieving this goal.